Pengaruh Indeks Pembangunan Manusia, Pendapatan Perkapita dan Zakat terhadap Pertumbuhan Ekonomi Kabupaten Mandailing Natal - Samsi Efendi; Isnaini Harahap; Muhammad Ikhsan Harahap (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the effect of the Human Development Index (HDI), per capita income, and zakat funds on economic growth in Mandailing Natal Regency. This study used a quantitative approach with secondary time-series data for 2014–2025 obtained from the Central Statistics Agency (BPS) and the National Amil Zakat Agency (BAZNAS). Data were analyzed using multiple linear regression, including classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results show that the HDI has a negative and significant effect on economic growth, while per capita income has no significant effect. Zakat funds also have a negative and significant effect on economic growth. Simultaneously, HDI, per capita income, and zakat funds significantly affect economic growth. The coefficient of determination (R²) of 0.430 indicates that 43% of the variation in economic growth is explained by the three independent variables, while 57% is explained by other factors outside the model. These findings suggest the need to improve human resource quality, expand productive employment opportunities, and optimize productive zakat management to support sustainable economic growth in Mandailing Natal Regency.